Thermal evolution, second phases, and sintering behavior of LaPO4·nH2O nanorods prepared by two different chemical synthesis routes. Issue 6 (July 2015) - Colomer, M.T.; Mosa, J.
Abstract: Thermal evolution and sintering behavior of LaPO4 · n H2 O, prepared by two different chemical synthesis routes, are presented in this work as a comparative study. The presence of polytrioxophosphate (La(PO3 )3 ) in the as-synthesized powders, as minor second phase, and its consequences on thermal and sintering behavior are also discussed. At temperatures 1000 °C, the samples suffer a weight loss that could be caused by the volatilization of P4 O10 during the incongruent melting of the polytrioxophosphate. Furthermore, the derivative curves of the linear shrinkage show peaks at temperatures higher than 1000 °C that can be also related to that process. HREM–SAED–XEDS showed an amorphous phase in samples calcined at 800 °C/12 h that surrounds the boundaries of La(PO3 )3 crystals and according to XEDS analyses corresponds to LaPO4 . In addition, a glassy phase is also detected at some grain boundaries in sintered samples after polishing and thermal etching.